Analisis Pengaruh Penggunaan Heatsink Terhadap Pendinginan Sistem Maisotsenko Cycle-Indirect Evaporative Cooling Dengan Variasi Aliran Udara Menggunakan Komputasi Dinamika Fluida - Wysnawan, Anditya Putra; Wijaksana, Hendra; Ghurri, Ainul (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract Maisotsenko Cycle-Indirect Evaporative Cooling (M-IEC) is increasingly recognized as an environmentally friendly solution to address efficiency challenges in cooling systems. This cycle employs an indirect cooling principle that significantly reduces water and energy consumption, making it an attractive option for mitigating environmental impacts of cooling processes. Testing involved conducting simulations on M-IEC using ANSYS Fluent software. Simulations varied airflow speeds at 5 m/s, 7 m/s, and 9 m/s, and compared heatsink and non-heatsink configurations on the product channel wall. Increasing the heat transfer surface area or using a heatsink resulted in a more significant decrease in outlet temperature product channel. Conversely, without a heatsink, the temperature drop was less pronounced, affecting Dry Bulb Temperature Drop, Wet Bulb Effectiveness, Dew Point Effectiveness, Cooling Capacity, and Energy Efficiency Ratio (EER), demonstrating better performance with heatsink usage compared to without. Keywords: Ansys Fluent, Cooling system efficiency, Heatsink, Airflow velocity, Maisotsenko Cycle-Indirect Evaporative Cooling.